Hyperthermia with radiotherapy reduces tumour alpha/beta: Insights from trials of thermoradiotherapy vs radiotherapy alone. (September 2019) - Datta, Niloy R.; Bodis, Stephan
Graphical abstract: Highlights: Hyperthermia is known to inhibit postirradiation DNA damage repair. This could alter the α/β values in tumours. α/β were estimated from 12 clinical trials of thermoradiotherapy vs radiotherapy. α/β with thermoradiotherapy was computed as 2.25 Gy (95% CI: 1.8–2.7). This should guide in optimizing thermoradiotherapy dose-fractionation schedules. Abstract: Purpose: Hyperthermia inhibits the repair of irradiation-induced DNA damage and thereby could alter the α/β values of tumours. This study estimates the clinical α/βHTRT values from clinical trials of thermoradiotherapy (HTRT) vs radiotherapy (RT) in recurrent breast (RcBC), head and neck (III/IV) (LAHNC) and cervix cancers (IIB-IVA) (LACC). Methods: Three recently published meta-analyses for HTRT vs RT in RcBC, LAHNC and LACC were evaluated for complete response (CR). Studies with specified RT dose (D), dose/fraction (d) and corresponding CRs were selected. Tumour biological effective dose (BED) for each study with RT (BEDRT ) was computed assuming an α/βRT of 10 Gy. As outcomes were favourable with HTRT, thermoradiobiological BED (BEDHTRT ) was calculated as a product of BEDRT and %CRHTRT /%CRRT . The α/βHTRT was estimated as Dd/(BEDHTRT – D). Results: 12 trials with 864 patients were shortlisted – RcBC (3 studies, n  = 259), LAHNC (5 studies, n  = 338) and LACC (4 studies, n  = 267). Overall risk difference of 0.28 favoured HTRT ( p  < 0.001). Mean BEDRT and BEDHTRT were 64.7 Gy (SD: ±15.5) and 109.5 Gy (SD: ±32.1) respectively and global α/βHTRT was 2.25 Gy (SD: ±0.79). Mean α/βHTRT for RcBC, LAHNC and LACC were 2.05 Gy, 1.74 Gy and 3.03 Gy respectively. On meta-regression, α/βHTRT was the sole predictor for the corresponding risk differences of the studies (coefficient = −0.096; p  = 0.03). Conclusion: Thermoradiobiological effects on the repair of RT induced DNA damage results in reduction in α/β values of tumours. This should be considered to effectively optimize HTRT dose-fractionation schedules in the clinic.